Correlation between Protein Intake, Fat Free Mass, and Total Lymphocyte Count with Quality of Life in Pulmonary Tuberculosis Patients Undergoing Intensive Phase Treatment in Pekanbaru, Riau Province - Dewi Krisna Yunda; Fiastuti Witjaksono; Fariz Nurwidya (Molecular and Cellular Biomedical Sciences, 2020)
Background: Malnutrition and tuberculosis (TB) have a bidirectional relationship, which interacts between each other. In chronic infection, there is an imbalance between protein degradation and protein synthesis which marked with the loss of fat-free mass (FFM). Malnutrition can cause the atrophy of the thymus gland resulted in the reduction of lymphocyte production. Malnutrition in TB patients will reduce the quality of life. On the other hand, a good quality of life will increase the treatment success rate and decrease the risk of morbidity and mortality. Materials and Methods: A cross-sectional study was conducted in 12 primary health centers (PHC) chosen randomly from 23 PHC in Pekanbaru, Riau Province. The random selection was performed by using simple random sampling (random number generator). Data were collected from May until July 2019. Samples were selected using a consecutive sampling method and 72 subjects fulfilled all research criteria. The interview was used to collect basic characteristic data, dietary intake data, and quality of life score. Anthropometric measurement (body weight, body height, and FFM) and laboratory examination (total lymphocyte count) were done.Results: Research showed median age subjects was 33 years old (18-59 years old). Most of the subjects were male (56.9%), had a middle level of education, low income, were active smokers with underweight nutritional status. More than 50% of subjects had low protein intake, low fat-free mass, normal lymphocyte count and had a good quality of life.Conclusion: There was a statistically significant correlation between fat-free mass with PCS (r=0.239, p=0.044), but not for protein intake and total lymphocyte count.Keywords: fat-free mass, protein, quality of life, total lymphocyte count, tuberculosis